2009
DOI: 10.13031/2013.28853
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Scale Electrostatically Assisted Wet Scrubber for Controlling Dust in Livestock Buildings

Abstract: A prototype electrostatically assisted particulate wet scrubber (EPWS) for controlling dust in livestock buildings was developed and tested under laboratory and field conditions. Under laboratory conditions, the EPWS with the negatively-charged water spray had significantly higher particle removal efficiency (79%) than either the uncharged wet scrubber (58%) or the control (i.e., only the fan was operated; 21%). There was no significant difference in removal efficiency between the negatively-charged EPWS (79%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In addition to the economic feasibility, WES also has the technological rationality in that it signicantly increases the collection efficiency of submicron particles 16,[20][21][22] because all charged droplets suspended in the tower are highly efficient moving collectors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the economic feasibility, WES also has the technological rationality in that it signicantly increases the collection efficiency of submicron particles 16,[20][21][22] because all charged droplets suspended in the tower are highly efficient moving collectors.…”
Section: Introductionmentioning
confidence: 99%
“…Almuhanna et al [27,28] evaluated an electrostatically assisted particulate wet scrubber (EPWS) for dust control at swine facilities and found that the EPWS was effective in reducing airborne PM concentrations, with PM removal efficiencies of about 92% for PM 10 and 33-60% for PM 2.5 . Because a commercial electrostatic spraying device was used, the researchers were not able to study the effects of the key parameters, such as droplet diameter and charging voltage, on the performance of the device.…”
Section: Introductionmentioning
confidence: 99%
“…In the past 30 years, extensive studies and experiments have been carried out to avoid the disadvantages, improve the atomization quality, and expand the applications of the electrostatically assisted twin-fluid atomization for processing different nozzles, electrodes, and charging methods and using a variety of theoretical, numerical and experimental approaches [8][9][10][11][12][13][14][15][16][17]. Compared to conventional atomization techniques mainly by means of the aerodynamic forces, the electrostatically assisted twin-fluid atomization device generates a desired size distribution and sufficient surface charge droplets, which could be facilitated to improve deposition on various targets especially on the underside of the part and significantly reduce the drift of small inhalable droplets due to electrical forces.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al designed an electrostatic spraying twin-fluid nozzle, experimentally studied the drops size and velocity distribution, and revealed the effect of surface charge and high voltage on spray characteristics [6]. Almuhanna et al developed a prototype electrostatically assisted particulate wet scrubber for controlling dust in livestock buildings and experimental data showed that charged water spray had significantly higher particle removal efficiency (79%) than either of the uncharged wet scrubber (58%) [16]. Wang et al developed electrostatic atomization utilizing a combined annular and needle electrode which was coupled with a twin-fluid atomization device and investigated the characteristics of atomization and motion of droplets of uncharged and charged spray [7].…”
Section: Introductionmentioning
confidence: 99%